A Qualitative Study on Barriers to Treatment and Control of Hypertension Among Patients at Dessie Referral Hospital, Northeast Ethiopia, Ethiopia: Healthcare Workers’ Perspective - Abaynew Y (Dove Medical Press, 2021)
Yeshewas Abaynew,1 Mohammed Hussien2 1School of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Health Systems Management and Health Economics, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Yeshewas AbaynewSchool of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaEmail yag2005@yahoo.comIntroduction: Hypertension is the leading cause of morbidity and mortality and accounts for 13% of all deaths and 7% of the disease burden in the world. Although the importance of controlling hypertension has been recognized for many years, the majority of patients with hypertension remain uncontrolled. Studies indicate a very low adherence to lifestyle modifications among patients in the study area. Hypertensive patients face set of problems associated with adherence to antihypertensive drugs and healthy lifestyle modifications.Objective: The objective of the study was to explore barriers to hypertension treatment and control from healthcare workers’ perspective and experiences at Dessie Referral Hospital, Ethiopia.Methods: Seven healthcare workers actively involved in managing hypertensive individuals at Dessie Referral Hospital were recruited for the study. Participants were purposively selected from outpatient, inpatient, and pharmacy departments. The required data were collected by the principal investigator on exit interviews. An interview guide was developed by reviewing previous literature. Interviews were semi-structured, 8– 20 minutes in duration, and designed to elicit healthcare workers’experiences and perceptions and conducted until data saturation was reached. All interviews were recorded, transcribed verbatim, and thematically analyzed. Each theme was supported by using the participants’ quotes.Results: Three themes emerged. The major barriers impacted patients’ medication adherence and healthy lifestyle modifications were common use of diets during social settings, low level of awareness, lack of resources, misconceptions about hypertension, use of traditional medicines, inadequate physical activities, and high cost of drugs.Conclusion: Patients’ misconceptions about hypertension, common use of diets during festivals, and inadequate physical activities were factors associated with inadequate blood pressure control. Healthcare workers should better understand the problems that hypertensive patients’ face, thus achieving better control.Keywords: hypertension, adherence, healthcare workers, barriers, control, perspective